Pemberdayaan UMKM Aghni Craft melalui Digital Marketing dengan LinkTree sebagai Media Penghubung Multiplatform - Putri, Bela Ananda; Octaviana, Bella; Elisaputri, Binti Dheta; Jannah, Binti Roikhatul; Oktavia, Churin (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2025)
Digital marketing plays a crucial role in improving the competitiveness of Micro, Small, and Medium Enterprises (MSMEs), including Aghni Craft, a handmade accessories business in Kediri. However, limited knowledge of digital platforms hinders optimal promotion and sales. This community service program aims to enhance Aghni Craft’s digital presence through LinkTree, which integrates multiple online platforms into a single accessible link. The method used involves Participatory Action Research (PAR), consisting of problem identification, training, implementation, and evaluation. The implementation of LinkTree has successfully streamlined Aghni Craft’s online marketing strategy, increasing accessibility and engagement on digital platforms such as Instagram, WhatsApp, and marketplaces. As a result, there was a noticeable increase in customer interactions and product orders. This initiative demonstrates the effectiveness of digital tools in strengthening MSMEs, making them more competitive in the digital economy. Sustainable adoption of LinkTree is expected to further support business growth and market expansion.